Cadaveric Skill Laboratory: A Cutting-edge Training Resource - Rani , Archana (Medical Research and Its Applications Vol. 2, 2024)
An accurate description of any body part—including the skin—cannot be given without an understanding of anatomy. Cadaveric Skills Lab offers the resources and facilities needed to run professional and graduate-level courses. In order to support the teaching and training of health care professionals through practical learning experiences, King George's Medical University, Lucknow, Uttar Pradesh, India, developed the Cadaveric skill lab for training and research.